FACTORS ASSOCIATED WITH POOR GLYCEMIC CONTROL AMONG TYPE 2 DIABETES MELLITUS IN INDONESIA - Rian Adi Pamungkas; St. Hadijah; Andi Mayasari; Nusdin Nusdin (Belitung Raya Foundation, Indonesia, 2017)
Background: Type 2 Diabetes mellitus becomes the public health problem worldwide. Reasons for poor glycemic control in Type 2 diabetes are complex.Objectives: To determine factors contributed to poor glycemic control among Indonesian patients with Type 2 Diabetes mellitus.Methods: This was a cross sectional regression study. There were 70 respondents selected using purposive sampling. Pre-structured questionnaires were used to measure socio demographic, clinical characteristics, self-care management behaviors, medication adherence, barriers to adherence, and family support. Data were analyzed using chi-square and binary logistic regression.Results: Poor glycemic control was defined as HbA1c ≥7% or FBG ≥200 mg/dl. Findings of this study reported that 83% patients had or FBG ≥200 mg/dl, which confirmed as poor glycemic control. Logistic regression showed that increasing duration of diabetes (> 5 years), non-adherence to dietary behaviors recommendation through selecting healthy diet, arranging a meal plan, recognizing the amount calorie needs, managing dietary behaviors challenges, medication adherence, and family support were significantly influence poor glycemic control with increased odds ratio scores.Conclusion: The proportion of patients with poor glycemic control was raised. Increasing duration of diabetes, non- adherence to medication and dietary behaviors management, and lack of family support were associated with poor glycemic control. Thus, integration of diabetes self-management program with social support is needed to deal with patients’ need to achieve the great benefits in diabetes care.